2022
DOI: 10.7554/elife.75660
|View full text |Cite
|
Sign up to set email alerts
|

De novo-designed transmembrane domains tune engineered receptor functions

Abstract: De novo-designed receptor transmembrane domains (TMDs) present opportunities for precise control of cellular receptor functions. We developed a de novo design strategy for generating programmed membrane proteins (proMPs): single-pass α-helical TMDs that self-assemble through computationally defined and crystallographically validated interfaces. We used these proMPs to program specific oligomeric interactions into a chimeric antigen receptor (CAR) that we expressed in mouse primary T cells and found that both i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 80 publications
0
20
0
Order By: Relevance
“…When the designs are small (<100 amino acids), they may be subjected to atomistic forward‐folding ab initio simulations to verify that the sequences favor the designed conformation over others. 1 , 2 , 3 , 45 In large proteins, however, accurate forward‐folding simulations were until recently impossible. Our results demonstrate that the deep‐learning based method AlphaFold2 can shed light on design foldability even in large proteins that exhibit more than 100 mutations from any natural protein.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When the designs are small (<100 amino acids), they may be subjected to atomistic forward‐folding ab initio simulations to verify that the sequences favor the designed conformation over others. 1 , 2 , 3 , 45 In large proteins, however, accurate forward‐folding simulations were until recently impossible. Our results demonstrate that the deep‐learning based method AlphaFold2 can shed light on design foldability even in large proteins that exhibit more than 100 mutations from any natural protein.…”
Section: Discussionmentioning
confidence: 99%
“…As a general rule, design studies, particularly ones devoted to backbone design, often reveal significant deviations between experimental structures and design conceptions. When the designs are small (<100 amino acids), they may be subjected to atomistic forward‐folding ab initio simulations to verify that the sequences favor the designed conformation over others 1–3,45 . In large proteins, however, accurate forward‐folding simulations were until recently impossible.…”
Section: Discussionmentioning
confidence: 99%
“…It has also been shown that TMD modifications do not directly affect the antigen-binding or signaling domains of CAR, suggesting that this strategy could help develop CAR T-cell therapies with optimal safety and efficacy profiles. 23 …”
Section: Structural Design Of Chimeric Antigen Receptor (Car)mentioning
confidence: 99%
“…The TM domain is often derived from CD8 or CD28 molecules and functions to anchor CAR in the membrane and facilitate signal transduction. The choice or engineering of TM domain may affect the interactions between CAR molecules themselves 41 , or with other endogenous molecules such as CD28. 42 Innovative designs in hinge and TM domains may provide opportunities to tune CAR signalling.…”
Section: Hinge and Transmembrane Domainmentioning
confidence: 99%